Brand name, image, word of mouth towards buying habits and customer loyalty online shop - Sari, Desak Made Febri Purnama; Pradhana, I Putu Dharmawan (International Research Journal of Management, IT & Social Sciences, 2018)
The public consumption pattern was a subject to change with the era development. Wherein, the many demands to be able to avail goods or services without efforts to come transact. Therefore, Online shop term becomes familiar in the present to enter a very tight trading competition. Thus, it was necessary to analyze how high the influence of brand name and image, word of mouth influence buying habits and how high influence consumer loyalty to continue to choose an online shop. The research was intended to know the influence of brand and image, word of mouth for a product with its simple trade concept through technology media that can be utilized in all circles. In conducting online surveys of data through questionnaires to obtain a valid data using questions. The inferential analysis in the present study was conducted by partial least square (PLS) method by using Smart PLS 3.0 M3 program. The steps were taken in the process of PLS. Regarding the result, R2 value for brand name, brand image, and word of mouth on buying habit was 0.356. Whereas the influence of brand name, brand image, word of mouth and buying custom to customer loyalty R2 value was 0.772. The value of q-square predictive relevance (Q2), yields a number was 0.8532. Brand name to buying habits variable was 0.367 with the t-statistic condition was 2,432 > t - table 1.96 (accepted). Brand Name variable to customer loyalty variable was 0,242 with status of t - statistic equal to 3,324 > t-table 1,96 (accepted). Brand image to buying habit variable was 0.120 with state of t-statistics was equal to 0,965 < t-table 1,96 (rejected). Brand image to customer loyalty variable was 0,342 with condition t-statistic equal to 5,235> t-table 1,96 (accepted). Word of mouth to buying habit variable was 0.180 with the state of t-statistics was 1,214 < t-table 1,96 (rejected). Customers loyalty of customer variable was 0,309 with state of t-statistic was  4,140 > t-table 1,96 (accepted). Buying habit to customer loyalty variable was 0,156 with t-statistic was 2,415 > t - table 1,96 (accepted).